Executive dysfunction in children affected by obstructive sleep apnea syndrome: an observational study - Esposito M (Dove Medical Press, 2013)
Maria Esposito,1 Lorenzo Antinolfi,1 Beatrice Gallai,2 Lucia Parisi,3 Michele Roccella,3 Rosa Marotta,4 Serena Marianna Lavano,4 Giovanni Mazzotta,5 Francesco Precenzano,1 Marco Carotenuto1 1Sleep Clinic for Developmental Age, Clinic of Child and Adolescent Neuropsychiatry, Department of Mental and Physical Health and Preventive Medicine, Second University of Naples, Naples, Italy; 2Unit of Child and Adolescent Neuropsychiatry, University of Perugia, Perugia, Italy; 3Child Neuropsychiatry, Department of Psychology, University of Palermo, Palermo, Italy; 4Department of Psychiatry, Magna Graecia University of Catanzaro, Catanzaro, Italy; 5Unit of Child and Adolescent Neuropsychiatry, AUSL Umbria 2, Terni, Italy Introduction: The role of sleep in cognitive processes can be considered clear and well established. Different reports have disclosed the association between sleep and cognition in adults and in children, as well as the impact of disturbed sleep on various aspects of neuropsychological functioning and behavior in children and adolescents. Behavioral and cognitive dysfunctions can also be considered as related to alterations in the executive functions (EF) system. In particular, the EF concept refers to self-regulatory cognitive processes that are associated with monitoring and controlling both thought and goal directed behaviors. The aim of the present study is to assess the impact of the obstructive sleep apnea syndrome (OSAS) on EF in a large sample of school aged children. Materials and methods: The study population comprised 79 children (51 males and 28 females) aged 7–12 years (mean 9.14 ± 2.36 years) with OSAS and 92 healthy children (63 males and 29 females, mean age 9.08 ± 2.44 years). To identify the severity of OSAS, an overnight respiratory evaluation was performed. All subjects filled out the Italian version of the Modified Card Sorting Test to screen EFs. Moreover, to check the degree of subjective perceived daytime sleepiness, all subjects were administered the Pediatric Daytime Sleepiness Scale (PDSS). Results: No significant differences between the two study groups were found for age (P = 0.871), gender (P = 0.704), z-score of body mass index (P = 0.656), total intelligence quotient (P = 0.358), and PDSS scores (P = 0.232). The OSAS children showed a significantly higher rate of total errors (P < 0.001), perseverative errors (P < 0.001), nonperseverative errors (P < 0.001), percentage of total errors (P < 0.001), percentage of perseverative errors (P < 0.001), and percentage of nonperseverative errors (P< 0.001). On the other hand, OSAS children showed a significant reduction in the number of completed categories (P = 0.036), total correct sorts (P = 0.001), and categorizing efficiency (P < 0.001). The Pearson's correlation analysis revealed a significant positive relationship between all error parameters and apnea-hypopnea index, oxygen desaturation index, and percentage of mean desaturation of O2 with a specular negative relationship between the error parameters and the mean oxygen saturation values, such as a significant negative relationship between apnea-hypopnea index, oxygen desaturation index, percent of mean desaturation of O2, and the number of completed categories. Conclusion: Our study identified differences in the executive functioning of children affected by OSAS and is the first to identify a correlation between alteration in respiratory nocturnal parameters and EF that has not yet been reported in developmental age. These findings can be considered as the strength and novelty of the present report in a large pediatric population. Keywords: OSAS, polysomnography, executive functions, sleep, sleepiness, children